If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 94 + -4x = 2x + 16 Reorder the terms: 94 + -4x = 16 + 2x Solving 94 + -4x = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 94 + -4x + -2x = 16 + 2x + -2x Combine like terms: -4x + -2x = -6x 94 + -6x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 94 + -6x = 16 + 0 94 + -6x = 16 Add '-94' to each side of the equation. 94 + -94 + -6x = 16 + -94 Combine like terms: 94 + -94 = 0 0 + -6x = 16 + -94 -6x = 16 + -94 Combine like terms: 16 + -94 = -78 -6x = -78 Divide each side by '-6'. x = 13 Simplifying x = 13
| -9h+10=-5h-10 | | 6x+10=28 | | 17x=2(8x-4) | | -9-6d-9=-9d+9 | | 5-b=6b+5-7b | | T(10)=6n-4 | | 9+11x=119+x | | 12x^2-26x+8=0 | | 3t+10t+8=0 | | -q-9=-q-3q+6 | | 3x+5=2x+10 | | V(5)=7*3.14r^2 | | 3x+8=4x-3 | | 2x+35=x+70 | | 10x-7=8x+3 | | -9s=7-10s | | -22=3s+-8 | | 8d-2=10d | | 4(2a+3)=20 | | -10+y=10-3y | | 5y=x-7 | | 17=5-x | | 12-4x-6=2x+14 | | -7c=-6-5c | | 5y=-7+x | | 6x-4=-10 | | 2p=8-6p | | 13+-3p=-2 | | -4g+10=-3g | | 4x^3-x^5=0 | | 6x^2+8x-3=0 | | 9z=7z+10 |